2010
DOI: 10.1177/1065912910376390
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Out the Hook

Abstract: In this article the authors measure a phenomenon they name “exit talk”: the undertheorized pressures that second-place contenders for presidential nominations face to exit the race. Content analysis of media exit talk from the 2008 Clinton candidacy compared with that of key comparators from other modern presidential campaigns suggests that Clinton experienced greater levels of exit talk than her historical comparators, though less explicit pressure to exit than was exerted on Ronald Reagan in 1976. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Consequently, from late 2007 into January 2008 Clinton momentarily deviated from her dominant, masculine strategy and presented herself as a warmer, more feminine candidate to voters. 98 Figure 2 supports this analysis. This momentary shift in strategy marks an interesting point of disruption in her otherwise steady self-presentation up to that point in time.…”
Section: Clinton For President (2007-2008)supporting
confidence: 75%
“…Consequently, from late 2007 into January 2008 Clinton momentarily deviated from her dominant, masculine strategy and presented herself as a warmer, more feminine candidate to voters. 98 Figure 2 supports this analysis. This momentary shift in strategy marks an interesting point of disruption in her otherwise steady self-presentation up to that point in time.…”
Section: Clinton For President (2007-2008)supporting
confidence: 75%
“…52 Furthermore, front-runners may have a greater chance of setting the agenda than other candidates because "front-runners often have greater success than trailing candidates in getting their messages across in the news." 53 This benefit of access is compounded because other work has shown that candidates' influence on voter issue salience is most effective when the candidate and media agendas are emphasizing the same issues. 54 Taken together, front-runners at any point in the election derive several news coverage benefits because of access to the news media and potential to contribute to the setting of the agenda.…”
Section: Gender Issues and Traitsmentioning
confidence: 99%